2019
DOI: 10.1186/s41038-019-0150-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypocoagulation induced by broad-spectrum antibiotics in extensive burn patients

Abstract: Background Patients with extensive burns usually develop pro-coagulation soon after the injury if there is no sepsis occurred. We describe the case of an extensive burn adult suffering from hypocoagulation not related to sepsis, but secondary to antibiotic treatment. Case presentation Here, we report a case of an adult male patient suffering from flame burns of 45% total body surface area (40% full thickness) combined with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Itagaki and Hagino published a case of a patient with haemorrhagic shock after thoracentesis, which was attributed to anatomic abnormality of the intercostal artery and hypovitaminosis K due to restricted diet and antibiotic therapy [ 10 ]. Vitamin K deficiency-associated hypocoagulation in a patient with extensive burns receiving meropenem was only reversed upon discontinuation of the broad-spectrum antibiotic therapy [ 11 ]. Nomoto et al reported a case of a patient with schizophrenia and catatonia who was hospitalised due to aspiration pneumonia and demonstrated low vitamin K levels and INR prolongation resulting from antibiotic therapy with ampicillin/sulbactam and cefmetazole as well as long-term restriction of food intake due to negativism and stupor [ 12 ].…”
Section: Antibiotic Therapy and Its Impact On Vitamin K Bioavailabili...mentioning
confidence: 99%
“…Itagaki and Hagino published a case of a patient with haemorrhagic shock after thoracentesis, which was attributed to anatomic abnormality of the intercostal artery and hypovitaminosis K due to restricted diet and antibiotic therapy [ 10 ]. Vitamin K deficiency-associated hypocoagulation in a patient with extensive burns receiving meropenem was only reversed upon discontinuation of the broad-spectrum antibiotic therapy [ 11 ]. Nomoto et al reported a case of a patient with schizophrenia and catatonia who was hospitalised due to aspiration pneumonia and demonstrated low vitamin K levels and INR prolongation resulting from antibiotic therapy with ampicillin/sulbactam and cefmetazole as well as long-term restriction of food intake due to negativism and stupor [ 12 ].…”
Section: Antibiotic Therapy and Its Impact On Vitamin K Bioavailabili...mentioning
confidence: 99%
“…• Reduced formation of gut microflora menaquinones, for instance during prolonged antibiotic therapy (Liu et al 2019), particularly when dietary supply cannot replace it, because of restricted diet (Itagaki and Hagino 2019) or in neonates (Aziz and Patil 2015). • Reduced intake in the context of vomiting, possibly observed in hyperemesis gravidarum (Baba et al 2016).…”
Section: Benefits (Human Studies)mentioning
confidence: 99%
“…The prothrombin time (PT) or the activated partial thromboplastin time (APTT) is usually longer than the upper limits of normal ( Hiensch and Lee, 2021 ); therefore, DIC can often lead to abrupt and excessive bleeding complications and even death ( Hiensch and Lee, 2021 ). Early identification and timely correction of DIC in surgical patients or emergency department patients with significant bleeding are paramount to prevent death and other consequences of hemorrhage ( Liu et al, 2019 ). It has been reported that many kinds of medications, including vitamin K antagonists, direct oral anticoagulants, and antibiotics, could lead to DIC in the adult population ( Zengotita and Holt, 1986 ; Hall and Carson, 2012 ; Liu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Early identification and timely correction of DIC in surgical patients or emergency department patients with significant bleeding are paramount to prevent death and other consequences of hemorrhage ( Liu et al, 2019 ). It has been reported that many kinds of medications, including vitamin K antagonists, direct oral anticoagulants, and antibiotics, could lead to DIC in the adult population ( Zengotita and Holt, 1986 ; Hall and Carson, 2012 ; Liu et al, 2019 ). However, the current pediatric drug safety landscape, including clinical trials, is limited as it rarely includes children and relies on extrapolation from adults.…”
Section: Introductionmentioning
confidence: 99%